Effect of Nano-TiO2 Additives on the Corrosion Performance of Lubricating Oil on Steel 45 Substrates - Wang, Shizhao; Zhou, Xueqin; Liu, Dongzhi (Asian Journal of Chemistry, 2013)
An oleic acid modified TiO2 nanoparticles were synthesized by chemical co-deposition method. The surface morphology, size distribution and structure of the nanoparticles were analyzed by transmission electron microscopy, fourier-transform infrared spectroscopy and laser particle analyzer. The anticorrosion performance of oleic acid-TiO2 was examined by electrochemical techniques. It was found that the TiO2 nanoparticles with average diameter of 44 nm and combined with oleic acid by covalent bonds, were capable of being dispersed stable in oil, which enabled the nanoparticles to be used as additives in lubricating oil. The results of polarization curves and electrochemical impedance spectroscopy indicated that the addition of oleic acid-TiO2 nanoparticles in lubricating oil decreased the corrosion current density and increased the corrosion resistance of oil film on steel 45 substrates.